ETIOLOGICAL FACTORS CAUSING PURULOUS INFLAMMATION OF TOES AND HOOFS IN BREEDED CATTLE AND THEIR CLINICAL SIGNS (ResearchJet Journal of Analysis and Inventions, 2023)
The main feature of causing inflammatory infectious diseases is as a result of mechanical injuries, various injuries of animals occur, the contour of the hoof increases, the animal loses its appetite, and animals suffer severe pain during movement.